Research Analysis on Multi Representation in Physical Materials in The Year of 2014 to 2021 - Titin Sunarti (IJORER : International Journal of Recent Educational Research, 2022)
This research has the goal of analyzing the research of multi representation capabilities in physical matter. This research is a literature study with bibliometric analysis. Secondary data collection of research using Publish or Perish (PoP) in the form of articles of the last six years (2014-2021) on Google Scholar and Scopus. The results of the analysis of 19 research articles were analyzed based on the number of studies each year, VOSViewer visualization, multi representation of measured abilities including problem-solving, understanding concepts, student activities. The highest number of publications in 2021 was 6 articles, in 2015, 2016 there was no VOSViewer Visualization obtained by three dominant clusters. There are seven articles linking multi representation capabilities to problem-solving abilities for a variety of physical materials. The application of multi representation to the understanding of concepts in some materials has been carried out in as many as seven studies. This research is expected to be the next research reference in analyzing the application of appropriate learning models to improve the multi representation ability of learners for various levels of education.